Distribution of Authority for Mining Business Permits between the Central Government and Regional Governments After the Enactment of the Minerba Law Number 4 of 2009 - Cakranegara, Pandu Adi; Rahadi, Dedi Rianto; Susilowati, Etty (Journal of Progressive Law and Legal Studies, 2023)
Mining commodities are strategic commodities for the Indonesian people because they are a source of state revenue. On the other hand, mining has a significant social, economic, and political impact. Therefore, the decision to grant a mining permit needs to be considered carefully. The Minerba Law of 2009 took over some authority to the Central Government. This takeover creates a conflict in the Regional Government which wants the authority to grant permits to reside with the regional government. By using normative analysis, this study tries to see the purpose of the Minerba Law Number 4 of 2009. This research shows that apart from granting permits, other factors need to be considered, namely how the mining sector provides revenue and benefits the local community.